PERFIL DOS PROFESSORES DE CIÊNCIAS: o ensino de física no 9º ano no município de Monte Alegre-Pará - FALABELO, Alex Silva (2024)
The present work of course completion aims to trace the profile of some professors of Sciences (Physics) of the public network of the 9th grade of Elementary School in Monte Alegre. This will be done from the presentation of the methodologies used by the teachers in the classes and the identification of the main difficulties faced by these teachers. However, the importance of creating, providing, and researching new methods to help improve the quality of science education is highlighted here. Appropriate teaching methods can be a solution to the problems generated in science education, even if they escape the old traditional model of education. We chose a research based on the principles of the qualitative approach to this work. It was carried out surveys in data through questionnaires with and theoretical references related to the subject matter. It was used as a research sample, teachers who teach in the level fundamental and average some public schools of the municipality of Monte Alegre-Pará. The information collected was organized and analyzed in accordance with the principles of analysis established during this project. The results obtained with the application of the questionnaire demonstrate that the strategies used by most teachers of science are out theoretical ideal, which can lead to difficulties of learning for students. Yet, it is necessary that during the process of higher education, the teacher acquires techniques, Methods, strategies and tools appropriate and necessary for the performance of its function as a qualified professional for your area of expertise.